Interaction between Cannabinoid Type 1 and Type 2 Receptors in the Modulation of Subventricular Zone and Dentate Gyrus Neurogenesis - Rodrigues, Rui S.; Ribeiro, Filipa F.; Ferreira, Filipa; Vaz, Sandra H.; Sebastião, Ana M.; Xapelli, Sara (Frontiers in Pharmacology, 2017)
Neurogenesis in the adult mammalian brain occurs mainly in two neurogenic niches, the subventricular zone (SVZ) and the subgranular zone (SGZ) of the dentate gyrus (DG). Cannabinoid type 1 and 2 receptors (CB1R and CB2R) have been shown to differently modulate neurogenesis. However, low attention has been given to the interaction between CB1R and CB2R in modulating postnatal neurogenesis (proliferation, neuronal differentiation and maturation). We focused on a putative crosstalk between CB1R and CB2R to modulate neurogenesis and cultured SVZ and DG stem/progenitor cells from early postnatal (P1-3) Sprague-Dawley rats. Data showed that the non-selective cannabinoid receptor agonist WIN55,212-2 promotes DG cell proliferation (measured by BrdU staining), an effect blocked by either CB1R or CB2R selective antagonists. Experiments with selective agonists showed that facilitation of DG cell proliferation requires co-activation of both CB1R and CB2R. Cell proliferation in the SVZ was not affected by the non-selective agonist, but it was enhanced by CB1R selective activation. However, either CB1R or CB2R selective antagonists abolished the effect of the CB1R agonist in SVZ cell proliferation. Neuronal differentiation (measured by immunocytochemistry against neuronal markers of different stages and calcium imaging) was facilitated by WIN55,212-2 at both SVZ and DG. This effect was mimicked by either CB1R or CB2R selective agonists and blocked by either CB1R or CB2R selective antagonists, cross-antagonism being evident. In summary, our findings indicate a tight interaction between CB1R and CB2R to modulate neurogenesis in the two major neurogenic niches, thus contributing to further unravelling the mechanisms behind the action of endocannabinoids in the brain.